Otimizando a eficiência de células solares baseadas em nanoestruturas semicondutoras quaternárias - Thomen, Diana Maria Navroski (2020)
Solar cells composed of semiconductor materials with gap energies and different structures, commonly known as Multijunction, have been the record holders for efficiency in converting solar to electric energy in recent years. However, the cost associated with the difficulty of producing these cells is still a barrier to be overcomed for large-scale implementation in the face of traditional Silicon-based devices. One way to make them more attractive is to further improve their efficiency through the use of the appropriate materials and manufacturing conditions. In this sense, this work proposes the optimization of Multijunction solar cells through the growth of super-lattices composed of GaAsSb/GaAsN ternary alloys and with different period thicknesses, in addition to GaAs/GaAsN reference sample. Optical characterizations were carried out based on photoluminescence and time resolved photoluminescence. It was observed that the samples with larger period width have better crystalline quality in addition to having a slower optical recombination time, in which the gap of the material's energy can also be adjusted by varying the period width of the super-lattices. The lifetimes decay were evaluated, where the variation can be from tens of nanoseconds to hundreds of picoseconds, according to the spectral region of optical emission. The results of photoluminescence showed that the studied super-lattices are all type-II, which envision the application of these nanostructures in areas such as high efficiency solar cells.